2014
DOI: 10.1007/s10753-014-9884-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Carvacrol Propionate

Abstract: This study aimed at synthesizing the carvacrol propionate (CP) and evaluating its pharmacological profile. CP was obtained from carvacrol and propionyl chloride through an esterification reaction. Male Swiss mice were treated with CP (25, 50, or 100 mg/kg). We evaluated the analgesic effect, mechanical hyperalgesia, and anti-inflammatory effect. Pre-treatment with CP inhibited (p<0.01 and 0.001) the formalin-induced nociception in both phases. CP inhibited (p<0.05, 0.01, and 0.001) the development of mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The results of this experiment are matched with the results published by Santana et al These authors have achieved an antinociceptive effect of carvacrolpropionate when this derivate of monoterpene administered to mice orally in the same dosage range (25, 50, 100 mg/kg) in the pre-treatment of hyperalgesia caused by formalin [11]. Also, Bonfi t et al showed that isoproxy-carvacrol administered intraperitoneally (10,30, 100 mg/kg) in the pre-treatment of formalin-induced hyperalgesia in mice and in the pre-treatment of carrageenan-induced hyperalgesia in rats (paw pressure tests), achieved a signifi cant antinociceptive effect only at the highest dose (100 mg/kg) [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this experiment are matched with the results published by Santana et al These authors have achieved an antinociceptive effect of carvacrolpropionate when this derivate of monoterpene administered to mice orally in the same dosage range (25, 50, 100 mg/kg) in the pre-treatment of hyperalgesia caused by formalin [11]. Also, Bonfi t et al showed that isoproxy-carvacrol administered intraperitoneally (10,30, 100 mg/kg) in the pre-treatment of formalin-induced hyperalgesia in mice and in the pre-treatment of carrageenan-induced hyperalgesia in rats (paw pressure tests), achieved a signifi cant antinociceptive effect only at the highest dose (100 mg/kg) [19].…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that carvacrol administered orally in mice reduces formalin-induced nociception, mechanical hyperalgesia and infl ammation in damaged tissues [11]. Also, Guimaraes et al [12] demonstrated that carvacrol administered orally in mice exhibits signifi cant antinociceptive and anti-edematous activity on hyperalgesia and edema caused by carrageenan and tumor necrosis factor-alpha (TNF-α).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies found that (a) carvacrol enhanced warmth and heat pain on the human tongue; , (b) synthetic carvacrol propionate attenuates nociception, mechanical hyperalgesia, and inflammation in male Swiss mice through inhibition of cytokines; (c) oral administration of carvacrol in mice models of pain resulted in significant inhibition of nociception without impairment of motor performance, suggesting that the antinociceptive activity might not act through the opioid system; (d) results of a study of orofacial analgesic-like activity of carvacrol in rodents suggest that the compound might represent an important tool for the treatment of orofacial pain; (e) carvacrol in drinking water was more effective than the steroidal drug dexamethasone in mitigating adverse effects in sensitized guinea pigs, suggesting the monoterpene could be used to treat asthma in humans; and (f) Guimarães et al . reviewed mechanisms that might govern analgesic aspects of structurally different monoterpenes.…”
Section: Additional Bioactivities and Health-promoting Properties Of ...mentioning
confidence: 99%
“…Studies have shown that adding tannin to zein to prepare zein/tannin nerve conduit, can enhance the effect of zein nerve conduit and promote the regeneration of peripheral nerves [81]. Compared with carvacrol, carvacrol propionate formed by esterification of carvacrol with propionyl chloride in the presence of triethylamine (TEA) has stronger antiinflammatory, analgesic and antihyperalgesic functions [82], carvacrol esters and ethers with amino groups formed by functionalizing the phenolic group of carvacrol can be anchored to the gold surface to develop antibacterial coatings [83]. Thymol combined with nonsteroidal antiinflammatory drugs can reduce the production of reactive oxygen species and reduce the probability of adverse reactions such as gastric mucosal damage [84],which may be a new application of nonsteroidal anti-inflammatory drugs.…”
Section: Drug Loadingmentioning
confidence: 99%